Rapid detection of Enterovirus and Coxsackievirus A10 by a TaqMan based duplex one-step real time RT-PCR assay. (June 2017) - Chen, Jingfang; Zhang, Rusheng; Ou, Xinhua; Yao, Dong; Huang, Zheng; Li, Linzhi; Sun, Biancheng
Abstract: A TaqMan based duplex one-step real time RT-PCR (rRT-PCR) assay was developed for the rapid detection of Coxsackievirus A10 (CV-A10) and other enterovirus (EVs) in clinical samples. The assay was fully evaluated and found to be specific and sensitive. When applied in 115 clinical samples, a 100% diagnostic sensitivity in CV-A10 detection and 97.4% diagnostic sensitivity in other EVs were found. Highlights: A duplex real time RT-PCR assay for the detection of Enterovirus and Coxsackievirus A10 was developed. The assay was specific and sensitive and had been evaluated in 115 clinical samples. This method could be an useful alternative for routine surveillance of CV-A10 and other EVs.